Learning civil societies : shifting contexts for democratic planning and governance - Angeles, Leonora C.; Gurstein, Penny (Green College thematic lecture series., 2007)
As public issues stretch out to affect an ever expanding population, democratizing planning and governance becomes increasingly important. How localized communities embrace the progressive qualities of civil society is a critical topic in an era where diverse and divergent forces often counteract civil society formation and community initiatives. This collection explores the theoretical underpinnings of democratic planning and governance in relation to civil society formation and social learning. The contributors to this volume use multiple lenses to uncover the challenges of democratizing planning and governance, helping to create a better understanding of how civil societies learn from their experiences, and how these lessons might be applied in other contexts. Learning Civil Societies provides insights for developing a critical methodology for studying civil societies and their formations and suggests that new organizational mechanisms within and outside civil societies must be created if more democratic forms of planning and governance are to emerge, be revitalized, and become institutionalized in the coming decades.